ANALISIS PENGARUH KUALITAS PRODUK, POTONGAN HARGA, LOKASI STRATEGIS, DAN PENGGUNAAN MEDIA SOSIAL SEBAGAI SARANA PROMOSI TERHADAP KEPUTUSAN PEMBELIAN DI SE’I SAPI KANA YOGYAKARTA - Wicaksono, Andoko; Shita Lusi Wardhani (Jurnal Ekonomi Dan Bisnis, 2022)
The purpose of this research was to examine and determine the effect of product quality, price discounts, strategic location, and social media as promotional means of purchasing decisions at Se'i Sapi Kana Yogyakarta. The population in this research are people who have made purchase transactions at Se'i Sapi Kana Yogyakarta. The sampling technique was using the purposive sampling technique. The data obtained by distributing questionnaires via google form with 137 respondents. The results of this research indicate that: 1) product quality has a significant effect on purchasing decisions at Se'i Sapi Kana Yogyakarta, 2) discounts have a significant effect on purchasing decisions at Se'i Sapi Kana Yogyakarta. 3) strategic location has an effect but not significant on purchasing decisions at Se'i Sapi Kana Yogyakarta, 4) the use of social media as promotional means have a significant effect on purchasing decisions at Se'i Sapi Kana Yogyakarta.